Persepsi Penonton Remaja Perempuan Terhadap Sinetron Ikatan Cinta di Desa Medan Krio Kecamatan Sunggal Kabupaten Deli Serdang - Meifiana Silvia Rosa; Sori Monang; Abdul Karim Batubara (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2022)
This study is useful to determine the perception of adolescent girls towards the soap opera Ikatan Cinta in Medan Krio Village, Sunggal District, Deli Serdang Regency and to find out the differences in the perception of adolescent girls towards the soap opera Ikatan Cinta, both in terms of education and age. So the method used is a qualitative method with a descriptive approach. This study uses the Uses and Gratification theory. This theory was proposed by Elizu Katz, Jay G. Blumler and Michael Gurevitch. This theory shows that the main problem is not how the media changes the attitudes and behavior of the audience, but how the media meets the personal and social needs of the audience. The results of this study indicate that the Perception of Teenage Girls towards the soap opera Ikatan Cinta produces various kinds. One of the main things that makes this soap opera viral is the interesting storyline and also the visualization of players who fall into the standard of beautiful according to Indonesian people.